1987
DOI: 10.1002/art.1780300110
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characterization of synovial cells in arthritic mrl‐lpr/lpr mice

Abstract: MRL-lpr/lpr (MRWl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…In approximately 20% female MRL/ lpr mice at 12 weeks of age, any slight findings such as hyperplasia of synovial cells and mononuclear cell infiltration were observed. These findings of arthritis lesions in MRL/ lpr mice are consistent with those in previously demonstrated reports [50][53].…”
Section: Methodssupporting
confidence: 93%
“…In approximately 20% female MRL/ lpr mice at 12 weeks of age, any slight findings such as hyperplasia of synovial cells and mononuclear cell infiltration were observed. These findings of arthritis lesions in MRL/ lpr mice are consistent with those in previously demonstrated reports [50][53].…”
Section: Methodssupporting
confidence: 93%
“…Thus, in the MRL lpr/lpr mice the proliferating and infiltrating synovial cells to a large extent carried macrophage markers. However, most of these cells were negative for MHC class II expression and virtually no T cells could be detected close to the synovial lining or in the pannus either by conventional histology [71] or after immunohistochemical stainirlgs with the Lyt-1, anti-CD4 or anti-CD8 antibodies [83]; in parallel studies it was demonstrated that the applied methods were indeed sensitive enough to detect those T cells of these mice that display a low staining for these markers (the ,,dull" cells) [83]. It was concluded from these studies that the local pathogenetic process of MRL lpr/lpr mice differ from that of RA concerning the working hypothesis of a local and class II MHC-driven T cell activation and over-expression of MHC class II.…”
Section: Arthritis In Mrl Lpr/lpr Micementioning
confidence: 98%
“…The synovium is infiltrated by large numbers of transformed-appearing mesenchymal cells at the cartilage-pannus junction which express the macrophage marker Mac-1. Interestingly, class II expression by these cells is scarce and lymphocytes are completely absent or at a site distant from the foci of bone and cartilage erosion [72].…”
Section: Animal Modelsmentioning
confidence: 98%